Determination of Optimal Amikacin Dosing Regimens for Pediatric Patients With Burn Wound Sepsis. Issue 4 (July 2015) - Yu, Tian; Stockmann, Chris; Healy, Daniel P.; Olson, Jared; Wead, Stephanie; Neely, Alice N.; Kagan, Richard J.; Spigarelli, Michael G.; Sherwin, Catherine M. T.
Abstract : This study aimed to develop optimal amikacin dosing regimens for the empirical treatment of Gram-negative bacterial sepsis in pediatric patients with burn injuries. A pharmacodynamic (PD) target in which the peak concentration (Cmax ) is ≥8 times the minimum inhibitory concentration (MIC) (Cmax /MIC ≥ 8) is reflective of optimal bactericidal activity and has been used to predict clinical outcomes. Population pharmacokinetic modeling was performed in NONMEM 7.2 for pediatric patients with and without burn injuries. Amikacin pharmacokinetic parameters were compared between the two groups and multiple dosing regimens were simulated using MATLAB to achieve the PD target in ≥90% of patients with burn injuries. The pharmacokinetic analysis included 282 amikacin concentrations from 70 pediatric patients with burn injuries and 99 concentrations from 32 pediatric patients without burns. A one-compartment model with first-order elimination described amikacin pharmacokinetics well for both groups. Clearance (CL) was significantly higher in patients with burn injuries than in patients without (7.22 vs 5.36 L/h, P < .001). The volume of distribution (V) was also significantly increased in patients with burn injuries (22.7 vs 18.7 L, P < .01). Weight significantly influenced amikacin CL ( P < .001) and V ( P < .001) for both groups. Model-based simulations showed that a higher amikacin dose (≥25 mg/kg) achieved a Cmax /MIC ≥8 in ≥90% of patients with assumed infections of organisms with an MIC = 8 mg/L. Amikacin pharmacokinetics are altered in patients with burn injuries, including a significant increase in CL and V. In simulations, increased doses (≥25 mg/kg) led to improved PD target attainment rates. Further clinical evaluation of this proposed dosing regimen is warranted to assess clinical and microbiological outcomes in pediatric patients with burn wound sepsis.